Occupational carbon footprints and exposure to climate transition risks - Zengkai Zhang; Chuanzeng Zheng; Zhenyu Xiao; Kunfu Zhu (Nature Communications)
Abstract Workers, especially those involved in occupations with high carbon footprints, are more susceptible to the growing risks associated with the climate transition as a result of the urgent need to transition to a low-carbon economy. Here we trace the occupational carbon footprints along global value chains and estimate the associated exposure to climate transition risks. The volume of occupational carbon footprints is trending upward globally, with the expansion of primary labour inputs as the main driving factor. There is a considerable deal of territorial and occupational variance in carbon footprints from the perspectives of both volume and per worker. The most vulnerable to climate transition risks are drivers, craft workers and machine operators, particularly those operating in emerging countries. The current study’s findings may help the understanding of the role that workers play in climate change and the formulation of more targeted policies to protect vulnerable workers.